2017
DOI: 10.5812/iranjradiol.48000
|View full text |Cite
|
Sign up to set email alerts
|

The Normal Value of Tibial Tubercle Trochlear Groove Distance in Patients with Normal Knee Examinations Using MRI

Abstract: Patellar instability is a multifactorial common knee pathology that has a high recurrence rate, and the symptoms continue and ultimately predispose the patient to chondromalacia and osteoarthritis. Tibial tuberosity-trochlear groove distance (TTTG) is very important in the assessment of patellofemoral joint instability. The purpose of this study was to report normal value of TTTG in males and females in different age groups and to assess the reliability of MRI in measuring TTTG. All patients presenting with kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 0 publications
1
15
0
2
Order By: Relevance
“…In this study, we investigated the relationship between TT position, TT-TG distance, and internal/external rotation under weight-bearing conditions. The TT-TG distance values ranged between 5-17 mm in extension, which is considered as being normal [12,13]. Our results showed an overall tendency of decreased TT-TG distance values over knee flexion, which coincides with previous findings [8,7].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we investigated the relationship between TT position, TT-TG distance, and internal/external rotation under weight-bearing conditions. The TT-TG distance values ranged between 5-17 mm in extension, which is considered as being normal [12,13]. Our results showed an overall tendency of decreased TT-TG distance values over knee flexion, which coincides with previous findings [8,7].…”
Section: Discussionsupporting
confidence: 90%
“…In the study by Pandit et al [11], 100 patients with suspected meniscus injury and normal arthroscopy were examined, and the mean TT-TG distance was found to be 10 ± 1 mm; 9.91 mm in males and 10.04 mm in females, while Wittstein et al [13]found the mean value of TT-TG distance to be 9.4 ± 0.6 mm. In another study, Schoettle et al [12] compared the reliability of CT scanning with MRI and calculated the mean TT-TG value as 13.5 ± 4.6 mm on MRI, which is higher than the value reported by Pandit et al [11] and Sobhanardekani et al (14). Hingelbaum et al compared the MRI scans of 200 knees using similar to Shoettle et al method and found that the TT-TG values of the different sexes were not statistically different, with the mean TT-TG distance in the control group being 7.5 ± 3.5 mm compared to 13.5 ± 4.1 mm in the patient group [15].…”
Section: Discussionmentioning
confidence: 74%
“…Hingelbaum et al compared the MRI scans of 200 knees using similar to Shoettle et al method and found that the TT-TG values of the different sexes were not statistically different, with the mean TT-TG distance in the control group being 7.5 ± 3.5 mm compared to 13.5 ± 4.1 mm in the patient group [15]. In the study conducted by Sobhanardekani et al [14]in Iranian patients, the mean TT-TG distance was reported to be 10.9 ± 2.5 mm, with similar TT-TG values between sexes. In the adult Indian population, the mean normal value of the TT-TG distance was calculated as 13.54 ± 6.22 mm (13.19 ± 6.28 mm in males; 14.07 ± 6.06 in females) [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When TT-TG measurement is necessary, the CT study can be substituted by an axial T1-weighted sequence of the knees using the body coil, removing the need of unnecessary radiation exposure in this setting and, most importantly, allowing the use of the same threshold (15-20 mm) classically used in CT. Our study also confirms the excellent interrater reliability of MRI measurements, which had already been shown in previous studies. 14,17,18 Schoettle et al 19 compared knee CT and MRI (with a routine knee protocol) and found an excellent intermethods reliability, stating that additional CT scans were not necessary. However, many later studies have not been able to reproduce these results, concluding that CT and MRI TT-TG measurements are not equivalent, and that MRI measurements are systematically underestimated, 3,4,7-9 which suggests it would be inaccurate to use the same threshold in MRI and CT in diagnosis and surgical planning.…”
Section: Discussionmentioning
confidence: 99%